Hubungan Spiritualitas Terhadap Tingkat Stress Mahasiswa Semester Akhir Program Studi S1 Keperawatan - I Komang Dananda Saputra Nesa; G. Nur Widya Putra; Ni Luh Linda Ayuni Tania (Hospital Majapahit (JURNAL ILMIAH KESEHATAN POLITEKNIK KESEHATAN MOJOKERTO), 2025)
Final assignments are a frequent source of stress for students. Strong spirituality can increase motivation, reduce anxiety, provide a sense of calm, and foster confidence that future events will have a positive impact. The novelty of this research lies in its focus on examining the relationship between spirituality and stress among final-semester nursing students in Bali, specifically at STIKes Buleleng, a region that has not been widely studied and rarely uses the DSES and DASS instruments simultaneously.This study aims to determine the relationship between spirituality and stress levels among final-semester undergraduate nursing students at STIKes Buleleng. This study was quantitative with an observational design with a cross-sectional approach. Data collection used the DSES and DASS questionnaires, using a purposive sampling technique, with a sample size of 71 students. The Spearman correlation test yielded a value of -0.459 with a significance level of 0.000 (<0.05). The negative correlation value indicates that there is an inverse relationship between spirituality and stress levels, meaning that the higher a person's spirituality, the lower the stress level experienced. From this study, it can be concluded that there is a relationship between spirituality and stress levels of final semester students of the Nursing Undergraduate Program at STIKes Buleleng. Institutions need to strengthen spiritual development programs, provide counseling services and stress management training, form student support groups, improve academic guidance, and encourage further research with a wider sample and additional variables to understand the factors that influence final semester student stress